Overview of higher education funding models - Varga, Balázs; Vincze, Szilvia (Acta Agraria Debreceniensis, 2014)
t can be defined in the course of the review of the financing characteristics of higher education that every model has its advantageous feature which is missing from the others, at the same time; it has its weaknesses as well. None of the basic models can meet the complex requirements of the nowadays society and government, thus the choice between the models have to be based on the preferences of decisionmakers and society. In most countries the combination of models are implemented, which compensate the weaknesses of the basic models, however, the models formed by the combination of different principles are neither perfect.